The Challenges of Quality in Higher Education: Reviewed Book of Higher Education on the Horizon of 2030, by OCDE - Mekki Saadallah (Sultan Qaboos University, 2016)
Most of the developed countries in the world care about quality and the guarantee of education because it is considered as the basic pillars of the efficacious human development. In light of the basic transformations of the higher education, the organization for economic cooperation and development (OECD) has issued a book in two parts entitled "Higher Education in 2030". The first part treats the theme of "demography" and its impact on the future of the higher education in the context of two major indices; the aging of the European society and the growing of the ethnic diversity emerging from the regulated and illegal immigration. In the second part, the researchers expose the phenomenon of "Globalization", its manifestations and its effects on the higher education, especially those which are attached to private investments; to the establishment of the private universities; to the internationalization of the higher education and to its overtaking of the national and continental borders. The search presents the most important ideas and themes contained in the book for stimulating the interest about the future of the quality in the higher education and clarifying the approaches reached by the global research to improve the quality of training.